The effects of recovery duration on physiological and perceptual responses of trained runners during four self-paced HIIT sessions - Schoenmakers, P. P. J. M.; Reed, K. E. (Journal of Science and Medicine in Sport, 2019)
Objectives: This study aimed to examine the effects of different recovery durations on self-selected running velocities, physiological responses, and ratings of perceived exertion (RPE) in a commonly used high intensity interval training (HIIT) protocol.